Body Image Problems and Disordered Eating Behaviors in Italian Adolescents With and Without Type 1 Diabetes: An Examination With a Gender-Specific Body Image Measure - Troncone, Alda; Cascella, Crescenzo; Chianese, Antonietta; Zanfardino, Angela; Piscopo, Alessia; Borriello, Anna; Casaburo, Francesca; del Giudice, Emanuele Miraglia; Iafusco, Dario (Frontiers in Psychology, 2020)
Objective: To examine body image problems and their associations with disordered eating behavior (DEB) in adolescents with type 1 diabetes (T1D) and well-matched healthy peers. Methods: Using a cross-sectional design, 183 adolescents with type 1 diabetes (13.02–18.05 years) were recruited from diabetes centers in southern Italy and compared to healthy peers matched for age and gender. Participants completed self-report measures of DEB (DEPS-r, EDI3-RF) and a gender-specific body image problem questionnaire (SATAQ-4R). Socio-demographic and clinical data (zBMI, HbA1c, disease duration) were also collected. Hierarchical multiple linear regression analyses were computed to determine the relative importance of diabetes variables and body image problems on participants’ DEBs after controlling for demographic variables. Results: Adolescents with T1D showed diabetes-specific eating problems in 37.7% of cases and had more eating problem symptoms in terms of drive for thinness, bulimia, and body dissatisfaction than healthy peers. Male adolescents with T1D did not display more body image problems (p>.05); females with T1D compared to females in the control group were found to be more pressured by family (p=.025) but less by media (p=.022) to improve their appearance and attain a thin body. zBMI and body image problems contributed to a significant increase in DEB risk both in male and female adolescents with T1D and in healthy peers (zBMI .213<𝛽<.426, p<.05; body image .243<𝛽<.572, p<.05). None of the variables analyzed were found to significantly predict male bulimic symptoms (all 𝛽 <.296, p>.05). Conclusions: Since in adolescence T1D and insulin therapy may increase the risk of weight gain and promote focus and attention on the body and thus contribute to the development of body image problems and DEBs, continuity of medical, nutritional, and psychological care is needed.